Multicultural Aspects in The Curriculum of Catholic Religious Education in First Middle School - Kristianus Kristianus; Magdalena Magdalena (JETL (Journal of Education, Teaching and Learning), 2022)
This research was motivated by the declaration of the year of religious tolerance in 2022. Of course, this tolerant attitude must be supported by the multicultural education that students receive. For this reason, it is necessary to examine whether there is a multicultural education content in Catholic Religion subjects taught in Junior High Schools. By reviewing the 2013 National Curriculum and conducting in-depth interviews with related parties according to qualitative methods. Finally, a surprising finding was found. It turns out that as long as students study Catholicism in Junior High School, they have learned 14 chapters of multicultural education from 29 chapters of learning and as many as 49 basic competencies out of 116 basic competencies that must be mastered by students. This means that Catholic students, when they graduate from junior high school, already have adequate provisions to living tolerantly with a multicultural society. It was also found that this multicultural content was in line with the core teaching of the Catholic religion. The conclusion of this study is that the declaration of the year of tolerance by the government in terms of teaching the Catholic religion has a fairly adequate basis